Application of the Precautionary Principle in Hazardous Waste Transportation: Environmental Law Study on Licensing and Supervision Systems - Frisca Imanuel Suryadi; Maret Priyanta; Nadia Astriani (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the application of the principle of prudence in the legal system for the transportation of hazardous and toxic materials (B3) in Indonesia through a case study of the sodium hydroxide (NaOH-48) leak by CV. Yasindo Multi Pratama in West Bandung Regency. The method used in this study is the doctrinal legal method with a normative juridical approach, accompanied by an empirical case study of violations of technical permits, vehicle feasibility, and driver certification in the B3 transportation process. The novelty of this research lies in the integration of analysis between the principle of prudence as an environmental law principle and the technical transportation licensing system, which has not been studied in depth in the context of cross-sectoral supervision. The results of the study show that the application of the precautionary principle is still not effective because of its formalistic nature, which has prevented its systemic implementation. Furthermore, weak coordination between agencies, low compliance with regulations by business actors, and the absence of adequate preemptive mechanisms in the form of education and socialization are also factors that hinder the effectiveness of this principle. This study concludes that the effective application of the principle of prudence in the transportation of hazardous materials requires a reformulation of policies that emphasizes the integration of preemptive, preventive, and repressive measures, while affirming the multiple responsibilities of the government as the holder of the public protection mandate and business actors as the main subjects of the principle of strict liability.